Kiss kiss bang bang [videorecording (DVD)] - Black, Shane; Downey, Robert, Jr., 1965-; Kilmer, Val, 1959-; Monaghan, Michelle; Bernsen, Corbin, 1954-; Halliday, Brett (Warner Home Video, 2005)
While fleeing from the cops, small time hood Harry Lockhart stumbles into an acting audition. He does so well he gets to go to Hollywood. While there, Harry pursues a girl he loved in high school and ends up geting caught up in twisted murder mystery. His only chance of getting out alive is a private detective named Gay Perry, who also works as a consultant for movies.